Studies on Vegetative Propagation of Colutea nepalensis Sims through Shoot Cuttings: a Potential Species for Cold Desert Afforestation - Sharma, Sandeep; Negi, P. S.; Thakur, K. S.; Kumar, Surinder (Indian Forester, 2004)
Colutea nepalensis is an important shrub of cold desert areas. A study was conducted to examine vegetative propagation of this species through shoot cuttings. The cuttings were collected from Pooh area of Kinnaur District of Himachal Pradesh during spring and autumn seasons and treated with IBA and IBA in combination with thiamine for induction and growth of adventitious roots under intermittent mist in sterilized sand. Assessments on rooting, sprouting, root number, root length, shoot number and shoot length on the cuttings were conducted after 120-days of treatments. Of these, IBA treatments significantly promoted adventitious rooting in shoot cuttings collected during spring but in combination with thiamine failed to produce any synergetic effects on induction and growth of adventitious roots. The highest rooting in that season (96.67%) was obtained from cuttings treated with 0.2% IBA + 0.05% Captan + 0.1% Sucrose. However, treatment of 0.1% IBA + 0.05% Captan+O.l% Sucrose is recommended as most economical treatment for mass propagation of Colutea nepalensis in mist chamber during spring season.